If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 6 = 5(x + -4) Reorder the terms: 6 + y = 5(x + -4) Reorder the terms: 6 + y = 5(-4 + x) 6 + y = (-4 * 5 + x * 5) 6 + y = (-20 + 5x) Solving 6 + y = -20 + 5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + y = -20 + -6 + 5x Combine like terms: 6 + -6 = 0 0 + y = -20 + -6 + 5x y = -20 + -6 + 5x Combine like terms: -20 + -6 = -26 y = -26 + 5x Simplifying y = -26 + 5x
| 3*(4+x)=27 | | 19-3.5/6-4= | | 10(x-1)=6(x+1) | | 3x=500 | | -2(x+6)+3=-11x+4(x+4) | | 10(x-1)=5/12 | | u-5=-4(v-1) | | 2-y/3=15 | | 7(7a+6)-1= | | 23ab-3a= | | 7+2[a+1]-3a=5a | | a-7=3(b+2) | | 500+90n=5000 | | 4u+24=6(u+3) | | a/2=14 | | 49r^2-84r+36= | | q-10=6(r+1) | | m+12=-5 | | x+6/4=-4x/16 | | 4x+4+5x+3=9x+7 | | 48r^2-84r+36= | | 0.25(5P-3)=0.75(3P-2) | | -6p=-3p+33 | | 2(d-1)=12(4d+3)+1 | | h(p)=p^2+2p | | x^2-25x+4x=52 | | -2u+6v=9 | | 11y+(2)3=-5y+24 | | 10y^2-7yz-6z^2= | | H/6-11=-22 | | 13(4x-3)=12 | | 12-23c=63-7c |